The Competitiveness of the Industrial Sector of the National Economies within the Setting of the Eurasian Economic Union - ORYNBET, Perizat; SEISEKENOVA, Meirambala Beisembekovna; SAKHANOVA, Gaukhar; LADANENKO, Yelena Ivanovna; KAPUSTYAN, Larisa A.; PURICHI, Vitalii V. (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019DO - 10.14505//jarle.v10.2(40).25, 2020)
This research examines the competitive advantages of the industrial sector of the national economies within the setting of the Eurasian Economic Union. The authors have analyzed a set of indicators of socio-economic development in the member states, including mutual and foreign trade, GDP, and key trends in industrial production. Special attention is devoted to the competitive advantages of Kazakhstan in the pharmaceutical and chemical industries. The authors have assessed the level of competitiveness of Kazakhstan-made products in the Union’s market place.